Psychische Gesundheit am Arbeitsplatz – Welche Rolle spielen sozioökonomische, geschlechterspezifische und migrationsbedingte Ungleichheiten? - Herold, Regina; Feißt, Manuel; Morawa, Eva; Hondong, Sinja; Rothermund, Eva; Waldmann, Tamara; Heming, Meike; Weber, Jeannette; Hander, Nicole R.; Mulfinger, Nadine; Kröger, Christoph; Erim, Yesim (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2024)
Background: Risk factors for mental health can be found in socio-economic-, gender- and migration-specific inequalities. These factors and the extent of depression, anxiety, and somatization among employees were examined in the present study. Methods: As part of the Early Intervention in the Workplace Study (friaa), mentally burdened employees at five locations in Germany were surveyed on socio-demographic-, work-, migration-, and health-related content. Regression analyses were used to examine the relationship between these factors and depression (Patient-Health-Questionnaire-9, PHQ-9), anxiety (Generalized Anxiety Disorder-2, GAD-2), and somatization (Somatic Symptom Scale-8, SSS-8) in the entire sample and in people with migration background (MB). For the latter, acculturation (Frankfurt Acculturation Scale, FRACC) and the perception of burden in terms of demands of immigration (Demands of Immigration Scale, DIS) were also taken into account. Results: On average, the 550 employees (12% with MB) showed clinically relevant depression (M = 13.0, SD = 5.1) (PHQ-9 ≥ 10), anxiety (M = 3.5, SD = 1.7) (GAD ≥ 3) and somatization (M = 13.0, SD = 5.8) (SSS-8 ≥ 12). Female gender was associated with higher anxiety and somatization. Older age and night shift work were associated with higher somatization. Discussion: The results confirm the high level of mental burden among this sample of employees in Germany. In order to maintain their mental health, support measures should be offered, especially for vulnerable groups such as women, older employees, and night shift workers.
CRIS-Team Scopus Importer:2024-06-28
Keywords: Acculturation; Depression; Gender differences; Migration; Working conditions